Students’ attitude towards the use of Flipped Classroom to teach listening comprehension - Lilian Celeste Pérez Castilla; Lilia Sulema Bórquez Morales; Martha Guadalupe Hernández Alvarado (Revista Lengua y Cultura, 2022)
This study explores students’ perspectives and experiences on the implementation of a flipped classroom model to develop listening comprehension. Within a qualitative data approach, using an open-ended questionnaire, information was collected from three university students chosen through convenience sampling. The data suggest that the implementation of this model improved students’ learning and motivation. By analyzing their responses using a content analysis method, the benefits perceived by the students who experienced the flipped classroom model were identified and grouped into five themes: Peer learning, Better preparation, Improved understanding, Motivation, and Autonomy. The findings of this study may be relevant not only for students but also for educators who are willing to improve their online teaching.